Virtual Exhibition Room of Megalitic Culture History in Bondowoso as a Source of History Learning for Bachelor's Degree - Arti Permata Sari; Agus Danugroho (Prodi. Pendidikan Sejarah FPIPS UPI dan APPS (Asosiasi peneliti dan Pendidik Sejarah), 2023)
This study discusses the presentation of a virtual exhibition space supported by digital media that is used as learning media for students. The history of megalithic culture is one of the subjects studied by students. There are still many problems that occur in learning this subject, so many students do not understand the lesson. With regard to these problems, researchers create learning media in the form of RPVs, or virtual exhibition rooms, which can solve problems related to learning media for the history of megalithic culture. Researchers collected material on the history of megalithic culture in Bondowoso. This study uses a qualitative descriptive method using literature and data that can strengthen the author's argument. Furthermore, researchers use the path that is distributed to students to determine the effectiveness of the learning media that have been created. The results of this paper state that providing virtual space, creating acceptable learning media, and being able to attract students' attention is not impossible because we have a lot of resources and technology that we can learn from. The many enthusiastic responses and positive reviews from students reflect the community's enthusiasm for aesthetic and technological advances as well as education. Indonesia continues to develop learning media wrapped in shared technology.